Watershed or Powershed? Critical Hydropolitics, China and the 'Lancang-Mekong Cooperation Framework'. Issue 3 (2nd July 2016) - Middleton, Carl; Allouche, Jeremy
Abstract: The countries sharing the Lancang-Mekong River are entering a new era of hydropolitics with a growing number of hydropower dams throughout the basin. Three 'powersheds', conceptualised as physical, institutional and political constructs that connect dams to major power markets in China, Thailand and Vietnam, are transforming the nature–society relations of the watershed. In the process, new conditions are produced within which the region's hydropolitics unfold. This is epitomised by the 'Lancang-Mekong Cooperation' framework, a new initiative led by China that proposes programs on both economic and water resource development, and anticipates hydrodiplomacy via China's dam-engineered control of the headwaters.